Structure and Variability of Indonesian Throughflow in Labani Canal - Rizqi Rizaldi Hidayat; Mukti Trenggono (Journal Omni-Akuatika, 2019)
Libani Canal is one of the areas which the flows water masses of the Pacific Ocean toward Indonesian seas. The existence of Mindanao current that affects an input of Indonesian Through-flow should be predicted. The influence of climate change on large scale circulation will affect the variations of physical condition. This study focused to investigate the variation of meridional Libani Current at 30 levels deep based on INDESO models data from January 2007 to January 2014. An area of interested was located at 4.16 °S and 117.92 - 119.42 °E. The results showed a strong current average reaches 0.5 m/s with a north-south orientation as the impact of bottom topography. Variations of current through Fourier analysis showed the annual and inter-annual fluctuations in the 365 days and 120-200 days related impacts strong El-Nino in 2009-2010. Spectrum energy density peaks in the 3 days and 53 days period that indicated as the impact of intra-seasonal variations.